1988 PUBLIC SMOKING PROGRAM YOUR MEMO OF 2/12 /88 - STUNTZ, SUSAN (Tufts Archival Research Center, 2007)
CONFIDENTIAL; Marginalia; Memorandum from Susan Stuntz to Ogilvy and Hather and Savarese and Associates regarding the 1988 Public Smoking program. Clarifies future action regarding workplace smoking campaigns among labor and in the media via third parties.